ChemInform Abstract: An Atom‐Economic Green Approach: Oxidative Synthesis of Functionalized 1, 4‐Dihydropyridines from N, N‐Dimethylenaminones and Amines. Issue 23 (June 2015) - Yu, Fu‐Chao; Zhou, Bei; Xu, Hui; Chang, Kwen‐Jen; Shen, Yuehai
Abstract The oxidative three‐component reaction between N, N‐dimethylenaminones and amines features an unusual oxidation of in situ formed dimethyl amine to provide the 4‐methylene bridge of the dihydropyridines formed.